CONCEPTUAL MODEL OF MARKETING MANAGEMENT FOR A SMALL INDUSTRIAL ENTERPRISE (World Bulletin of Management and Law, 2025)
The article examines the conceptual model of marketing management in small industrial enterprises as a strategic tool for enhancing competitiveness and ensuring sustainable development. The proposed model integrates key components such as strategic planning, market analysis, innovation management, and customer relationship management within the context of limited resources typical for small businesses. Particular attention is paid to the role of digital technologies and modern marketing instruments in optimizing business processes and adapting to dynamic market conditions. The study highlights the importance of systematic marketing management in strengthening the competitive position of small industrial enterprises in both domestic and international markets